Nobel students beget Nobel professors - Richard S.J. Tol (Tinbergen Institute, 2022)
It is unclear whether the hierarchy in the economics profession is the result of the agglomeration of excellence or of nepotism. I construct the professor-student network for laureates of and candidates for the Nobel Prize in Economics. I study the effect of proximity to previous Nobelists on winning the Nobel Prize. Conditional on being Nobel-worthy, students and grandstudents of Nobel laureates are not significantly more or less likely to win. Professors of Nobel Prize winners, however, are significantly more likely to win.
Keywords: Z13; A14; D85; 330; Network formation; Research training; Nobel prize